Characteristics and experiences of Chios breed - Zervas, N. P.; Hatjiminaoglou, J.; Georgoudis, A. (Agricultural and Food Science, 1988)
Discussed are the reproductive and productive characteristics of the dairy and prolific Chios sheep breed, originating from the homonymous Greek island. Besides the island, the breed is also raised in the Greek mainland, the westcoast of Turkey and in Cyprus. It is early maturing, with long reproductive reason and lambing period, extending from October to March. Inspite its high ovulation rate, repeatability estimates do not suggest the presence of fecundity genes. The average prolificacy ratio ranges between 1.80 and 2.0, with triplets and quadruplets not uncommon. The average exploitable milk yield varies between 180 and 200 kg, with occasionally reported productions of up to 400 and 500 kg. Repeatabilities of prolificacy and milk production based on island data were found 0.15 and 0.40, respectively. Heritability of milk yield from the island was 0.31 and 0.40, respectively, for second and third lactations. Recent estimates from Cyprus report values of 0.30 and 0.39 for 90-day milk and total milk yield, respectively. Other parameters and information on udder (mechanical milking), growth, and carcass characteristics as well as on crossbreeding trials are also reported. Some considerations are given with regard to potential and valorization of this highly productive sheep breed.